THE ROLE OF SHADOWING EDUCATIONAL TECHNOLOGY IN DEVELOPING ORAL SPEAKING COMPETENCE IN ENGLISH TEACHING (TAMADDUN NURI JURNALI, 2024)
This article presents the theoretical views of linguists on the importance of foreign languages in every field today and the development of oral speech competence in teaching English, and provides information about the important role of speaking and listening comprehension skills in teaching a foreign language. It has been stated that innovative educational technologies should be used in the development of oral competency, and that shadowing educational technology, considered one of the innovative educational techniques and methods, is effective in further improving speaking and listening comprehension skills in teaching English.